The Evaluation of the bond strength of heavyweight concrete containing iron pellets (Journal of Civil Engineering Researchers, 2025)
Heavyweight concrete incorporating iron aggregates is widely utilized as a radiation-shielding material in environments with harmful radiation due to its high density. Although this material is also employed as a structural component, certain mechanical properties, such as the bond strength between concrete and reinforcing steel bars, remain insufficiently studied. This paper investigates the bond strength of concrete containing varying percentages of iron pellets and its interaction with steel reinforcement. For this study, 25%, 75%, and 100% of the concrete aggregate was replaced with iron pellets, ensuring an appropriate grain size distribution. After curing under standard conditions, the specimens were subjected to direct pull-out tests. The results indicate that, except for the sample with 25% iron pellets, the inclusion of iron pellets slightly reduces compressive strength but enhances bond strength across all samples. Notably, adding 25% iron pellets combined with 5% micro silica in heavyweight concrete significantly improves compressive strength by 20% and bond strength by 43%.
Keywords: Heavyweight concrete; bond strength; iron pellets; pull out test